Les normes de gouvernance muséale au prisme du droit - Rivet, Michèle (Muséologies)

(untitled) (Association Québécoise de Promotion des Recherches Étudiantes en Muséologie (AQPREM), 2021)
The analysis of specific norms of museum governance in their entirety involves looking at hard law, which is secularly defined and strictly framed as state law. It also involves other rules or informal law, qualified as soft law or informal law, which bind the parties who adhere to them. This approach is adopted in this paper to first analyze international conventions, recommendations and declarations emanating from UNESCO, while also taking into consideration the rules qualified as soft law enacted by ICOM. Next, it examines the laws and regulations emanating from Canadian and Quebec legislators juxtaposed with the rules set out by the Canadian Museums Association and the Société des musées du Québec.UNESCO intervened on several occasions through conventions, which directly or indirectly affect museums, such as the Convention for the Safeguarding of the Intangible Cultural Heritage of 2003, or the 2005 Convention on the Protection and Promotion of the Diversity of Cultural Expression. Over the years, Several UNESCO recommendations have also been addressed to museums. In 2015, the General Conference of UNESCO adopted a Recommendation on the protection and promotion of museums and collections. This recommendation was born of a desire to replace and extend the application of existing standards and principles in international instruments, related to the museum’s position, as well as its role and responsibilities. To this international law is juxtaposed, as a flexible law, the standards enacted by ICOM. This has over the years, set out many standards and guidelines developed by the experts of the international committees. Museums or individuals who adhere to it indeed agree to submit to its rules. In Canada, the Museums Act only applies to the nine national museums (Canada Agriculture and Food Museum, Canada Aviation and Space Museum, Canada Science and Technology Museum, Canada Museum of History, Canadian War Museum, Canadian Museum for Human Rights, Canadian Museum of Immigration at Pier 21, Canadian Museum of Nature, National Gallery of Canada). However, laws and regulations also generally apply to all cultural institutions, the Copyright Act and the Cultural Property Export and Import Act among others. Quebec has, like all of Canada’s provinces, a specific law on museums which deals, as its federal counterpart, only with national museums. Montreal’s Museum of Fine Arts is interestingly governed by its own law, but what about the other 400 museums of Quebec? Here the Corbo Report, Entre mémoire et devenir, finds all its importance. In Quebec, the absence rather than the multitude of laws – hard law – can be questioned, though flexible norms appear very interesting. Pertaining to this topic, the Société des Musées du Québec [Quebec’s Museum Society] published in 2015 La gouvernance muséale, guide à l’intention des directions et des conseils d’administration. This guide describes what constitutes governance in the museum’s environment, it addresses the roles and responsibilities of museum administrators as well as their accountability and sets out a series of best practices in museum governance.It could therefore be said that a continuum exists at an international and national degree, between state norms, hard law and soft law norms, and as a range of graduated normativity, these constitute the outline of museum governance laws.